Students’ Perceptions of Online Presentations Via Zoom and in-Person Presentations in Improving Confidence in Speaking English - Hijril Ismail; Edi; Ilham; Asbah; Elsa Khusnul Khatimah (Arden Jaya Publisher, 2026)
This study examines presentations as an active learning strategy that can increase student engagement and confidence in speaking English. Although many studies have examined online learning, few have compared students' perceptions of Zoom presentations and in-person presentations in relation to increased confidence. This study aims to reveal students' perceptions of both forms of presentations, compare their advantages and disadvantages, and identify factors that influence confidence when speaking. The method used is descriptive qualitative with a population of students in the English Education Study Program (56 students) and a purposive sample who have presentation experience. Data were collected through a Likert questionnaire and in-depth interviews with 10 selected participants. Questionnaire analysis used descriptive statistics, while interview data were analyzed qualitatively through data reduction, presentation, and conclusion drawing. The findings show that presentations via Zoom can increase confidence for some participants because they reduce anxiety and are supported by technological features, despite being limited by technical problems and nonverbal interaction. Meanwhile, in-person presentations are more effective in training speaking skills, courage, and direct interaction with lecturers and classmates. The main factors that influence confidence are mastery of the material, support from the learning environment, and previous presentation experience. In conclusion, both forms of presentation complement each other, and integrating them into English language learning can provide a more holistic approach to improving participants' speaking confidence, communication skills, and adaptation in various communication situations.